The Impact of the (2011) Devaluation of the Swiss Franc on Eurozone Equity Benchmark Diversification - Broby, Daniel; Faessler, Raphael; Josavac, Milenko; Dehut, Christophe (International Journal of Economics and Financial Issues, 2016)
We investigate the diversification benefits of adding Switzerland to a Eurozone equity portfolio, both before and after the removal of Swiss franc peg to the euro. We use a mean-variance portfolio framework to compare the benchmark indices in the Eurozone, including a direct comparison between Switzerland and Germany as substitute market. We investigate the diversification effect both before and during the policy of a minimum exchange rate EURO/CHF. Furthermore, we compare the outcome of the mean-variance portfolio with an equally weighted portfolio composed out of a screened sample of both Swiss value and growth stocks. Our findings suggest that an equally weighted Swiss value portfolio (1/N) will generate the best risk adjusted performance when compared to a market capitalisation weighted index (MCWI) of Eurozone equities. We conclude that Eurozone investors would benefit from diversifying their portfolio with some exposure to the Swiss equity market and in particular Swiss value stocks. Keywords: company-specific political risk, Swiss stock market, portfolio diversification, optimal portfolios, currency, benchmark. JEL Classifications: G28, G14, P16